Optimalisasi Pengelolaan Jurnal Olahraga Papua (JOP) melalui Penguatan Tata Kelola Editorial di Fakultas Ilmu Keolahragaan - Hakim Irwandi Marpaung; Irfan Deni Oktavian; Swandika Pinem; Ince Abdul Muhaemin; Giofandi Samin (Universitas Negeri Gorontalo, 2026)
Papua Sports Journal (JOP) is a scientific publication of the Faculty of Sport Science, which plays a role in disseminating research and community service results in the field of sport. However, its management still faces various obstacles, such as optimizing the editorial process, link functions on journal pages, website appearance, and inconsistent content updates. This community service activity aims to optimize JOP management by strengthening editorial governance. The methods used include socialization, assistance in managing Open Journal Systems (OJS), improving the appearance and features of the website, and evaluating the implementation results. The activity involved a team of editors and journal managers from the Faculty of Sport Science. The results of the activity showed an increase in the editorial team's competence in OJS management, improving website functionality, updating content regularly, and improving the quality of journal governance. This program is expected to support more professional and sustainable JOP management, ready to meet national journal accreditation standards.